(untitled) (Neo Scientific Peer Reviewed Journal, 2025)
This article covers the process of treating various hollow hole surfaces with dorns. This process improves surface cleanliness, the quality level will be higher.In the design of deep holes of small diameter, it is desirable to use methods that provide high animosity and surface purity, the ability to work the details, as well as their rigidity, which is not less than HRC≤445. These include dornamon, flashing methods. Praised. Identification of technological deficiencies and defects in dornasiums and improvement of techniques and technologies of advanced methods of improvement and implementation in production are a means of increasing the efficiency of work efficiency.